2009
DOI: 10.1308/003588409x432121
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Internet by Patients Undergoing Elective Hernia Repair or Cholecystectomy

Abstract: INTRODUCTION Patient-directed informationa vailable on the internet is not always regulated; it may be confusing and sometimes just overwhelming. We aimed to establish the proportion of patients undergoing two common surgical procedures, who searched the internet for information about their operations and to assess the usefulness of the information they received.PATIENTS AND METHODS At otal of 105 consecutive patients undergoing elective abdominal wall hernia repair (n =5 4) or laparoscopic cholecystectomy (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Such low levels of decision-specific Internet use are consistent with other small-scale studies that have examined cancer screening but are much lower than reported use by other types of patients, including those diagnosed with prostate cancer, undergoing elective hernia repair, or cholecystectomy or genetic testing. [20][21][22][23] Furthermore, within the age group we studied, we found significant variation in Internet use for seeking health information by age, ranging from 38% for those aged 40 to 49 y to only about 14% for those older than 70 y. This negative association of age with use of the Internet is in line with other findings of lower Internet use among older cohorts.…”
Section: Ssupporting
confidence: 88%
“…Such low levels of decision-specific Internet use are consistent with other small-scale studies that have examined cancer screening but are much lower than reported use by other types of patients, including those diagnosed with prostate cancer, undergoing elective hernia repair, or cholecystectomy or genetic testing. [20][21][22][23] Furthermore, within the age group we studied, we found significant variation in Internet use for seeking health information by age, ranging from 38% for those aged 40 to 49 y to only about 14% for those older than 70 y. This negative association of age with use of the Internet is in line with other findings of lower Internet use among older cohorts.…”
Section: Ssupporting
confidence: 88%
“…1 In a consecutive series of 105 patients undergoing elective laparoscopic surgery, 31% with access to the internet used it to acquire information on their operation. 2 A similar picture exists in Germany with a reported 18% of patients using the internet prior to surgery. 3 In addition, the Department of Health (DH) has stated that 75% of all elective procedures should be performed as day cases.…”
mentioning
confidence: 66%
“…A study of 105 consecutive patients undergoing either elective abdominal wall hernia repair or laparoscopic cholecystectomy found that of the 77% of patients with internet access, 31% used it to acquire additional information about their operation and that in 26% this caused worry or confusion. 2 There is a diversity of sources providing information in the UK but the NHS as the major provider of healthcare should also act as the main provider of this information. Availability and quality of information is also critical to the provision of day surgery as a service.…”
Section: Discussionmentioning
confidence: 99%
“…it is well known that the internet contains huge amounts of potentially misleading information that can add to confusion and stress if not properly accessed or interpreted. 8 Our study highlighted that the majority of patients wished to receive both a leaflet and details of internet-based information sites. However, again, there was a significant age divide, with those aged <50 years more willing to accept internet access advice only while those aged ≥50 wanted a combination of the two but, preferentially, the hard-copy surgical information leaflet.…”
Section: Discussionmentioning
confidence: 87%